The global coal market : supplying the major fuel for emerging economies - Thurber, Mark C.; Morse, Richard K. (Cambridge, UK : Cambridge University Press, 2015)
"In the first decade of the twentieth century, the world witnessed tremendous upheaval in global energy markets. Oil markets were roiled by war and uprisings in the Middle East while economic expansion helped to push prices to near record (real) highs. Natural gas production in the United States was revolutionized with the emergence of new techniques for extracting shale gas. Nuclear power appeared on the verge of a dramatic expansion before its rise was cast into doubt by the tragic disaster at Fukushima. And renewable energy began to grow from a small contributor to world energy supplies into the one of largest sources of new electricity generation in many markets. Those narratives, for the most part, are well known. But one of the most important stories in modern energy markets remains largely untold and unappreciated, even as it is now reshaping the map of global energy use and the pace of climate change. That story is the story of coal's resurgence"--
Includes bibliographical references and index.
Keywords: Coal trade -- Developing countries; Energy consumption -- Developing countries; BUSINESS & ECONOMICS / Environmental Economics